Concrete Durability on Polimeric Waste - Kh., Kuldashev; A., Mallayev; Sh., Abduvohidov (European Journal of Life Safety and Stability (2660-9630), 2022)
There are given physic-properties results of concrete from polymeric material wastes and using of them in building material industry. The amount of complete residue of the coarse aggregate in the № 5 sieve is A20= 43% <50%, and the modulus of coefficient is Ms = 18.56<20, so the waste belongs to the group of coarse aggregates. Prepared mixes, which include wastes and Therefore, in terms of its granular composition, sand is considered suitable for concrete preparation, and it is recommended to improve its quality by adding polymeric waste to its granular composition for use in concrete preparation.